ANALISIS KOMITE AUDIT PADA PERUSAHAAN YANG MEMPEROLEH OPINI AUDIT PADA PERUSAHAAN MANUFAKTUR - Totok Susilo Pamuji Nugroho; Nina Adelina (Riset Manajemen dan Akuntansi, 2020)
This study aims to determine: (1) the factors that influence the provision of audit opinion, (2) the importance of audit opinion, and (3) the effect of audit opinion on manufacturing companies. The research method used is the study of literature that can assist researchers in finding references and can also be strong evidence in research. The results of study prove that: (1) the financial condition of the company is one of the factors giving an audit opinion in a company, (2) audit opinion very important for the company because it can help the company in preparing financial statements. Going concern audit opinions can also predict the viability of the company, and (3) audit opinion is very influential on the guarantee of truth and fairness of the financial statements company.